Fall frequency, predicting falls and participating in falls research: Similarities among people with Parkinson's disease with and without cognitive impairment. Issue 1 (January 2015) - Amar, K.; Stack, E.; Fitton, C.; Ashburn, A.; Roberts, H.C.
Abstract: Objective: We compared fall frequency and prediction among People with Parkinson's Disease (PwP) with and without cognitive impairment (CI); researchers sometimes overlook the former, concerned about consent, recall and adherence and differences in fall frequency and predictability. Methods: We recruited 101 PwP from one clinic, used the Montreal Cognitive Assessment to measure CI, noted repeated falls recalled retrospectively over 12 months and evaluated 'repeated falls' and 'difficulty turning' as predictors of falls over three months. Results: Participant median age was 76 years, and time since diagnosis 6 years. Of 40 participants without CI, 40% recalled falls and 55% fell during follow-up (1.9 (±3.8) falls/person), the sensitivity of fall history being 57% and of turning 36%. Of 36 participants with mild CI, 42% recalled falls and 42% fell during follow-up (1.2 (±1.8) falls/person), the sensitivity of fall history being 67% and of turning 69%. Of 25 participants with moderate CI, 60% recalled falls and 58% fell during follow-up (1.2 (±1.8) falls/person), the sensitivity of fall history being 71% and of turning 69%. Conclusions: Researchers need not exclude people with CI assuming falls are more frequent and less predictable than among those without. Fall rates (falls/person during follow-up) were similar among people with and without CI. Falls and difficulty turning were more sensitive predictors of falling in those with CI than those without: a simple mobility test may suggest an individual's risk of falling if a history is unavailable. Most PwP with moderate CI fall repeatedly: carer involvement facilitates their inclusion in research. Highlights: We examined 317 medicals records and 101 people with Parkinson's face-to-face. Records revealed cognitive impairment and postural instability in 46% of patients. 55% without cognitive impairment fell in 3 months versus 48% with. Predicting falls was similarly accurate with and without cognitive impairment. This study necessitated carer involvement and personalised telephone reminders.